Chirality Synchronization of Hydrogen‐Bonded Complexes of Achiral N‐Heterocycles. Issue 1 (29th November 2016) - Buchs, Jens; Vogel, Laura; Janietz, Dietmar; Prehm, Marko; Tschierske, Carsten
Abstract: 2, 4‐Diamino‐6‐phenyl‐1, 3, 5‐triazines carrying a single oligo(ethylene oxide) (EO) chain form an optically isotropic mesophase composed of a conglomerate of macroscopic chiral domains with opposite sense of chirality even though the constituent molecules are achiral. This mesophase was proposed to result from the helical packing of hydrogen‐bonded triazine aggregates, providing long‐range chirality synchronization. The results provide first evidence for macroscopic achiral symmetry breaking upon conglomerate formation in an amorphous isotropic phase formed by hydrogen‐bonded associates of simple N‐heterocycles that are related to prebiotic molecules. Abstract : Spontaneous symmetry breaking was achieved with simple achiral hydrogen‐bonded heterocycles that are related to prebiotic molecules by formation of conglomerates of chiral domains with opposite handedness. This optically isotropic mesophase was proposed to result from the helical packing of the hydrogen‐bonded triazine aggregates.